2014
DOI: 10.1186/1556-276x-9-589
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein expression of Caco-2 cells treated with selenium nanoparticles compared with sodium selenite and selenomethionine

Abstract: The study was designed to determine the differential protein expression of Caco-2 cells treated with different forms of selenium including sodium selenite, selenomethionine (Se-Met), and selenium nanoparticles (nano-Se). Two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and mass spectrometry (MS) were used to identify the differentially expressed proteins. The results indicated that seven protein spots, ubiquitin-conjugating enzyme E2 (E2), glutathione synthetases (GS), triosephosphate isomerase (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…In contrast, both Se doses caused well-marked decrease in total extracellular GSH [5]. The comparison of three Se-form (sodium selenite, selenomethionine and nanoparticles 100 nM of Se) revealed an increase in expression of glutathione synthase in Caco-2 cells, but two latter forms exerted a significantly greater effect [9]. In A549 human lung cancer cell line sodium selenite (0.5 mM) did not alter GSH content, while organic selenium (ethaselen 3 mM) and combination of these two forms caused GSH decrease, being intensified along the time of experiment [25].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, both Se doses caused well-marked decrease in total extracellular GSH [5]. The comparison of three Se-form (sodium selenite, selenomethionine and nanoparticles 100 nM of Se) revealed an increase in expression of glutathione synthase in Caco-2 cells, but two latter forms exerted a significantly greater effect [9]. In A549 human lung cancer cell line sodium selenite (0.5 mM) did not alter GSH content, while organic selenium (ethaselen 3 mM) and combination of these two forms caused GSH decrease, being intensified along the time of experiment [25].…”
Section: Discussionmentioning
confidence: 95%
“…Selenium generally caused a slight increase in SOD activity, but methylseleninic acid was the most effective form [21]. Fu et al also compared three Seform (sodium selenite, selenomethionine and nanoparticles at a dose of 100 nM of Se) and showed that expression of superoxide dismutase (Cu-Zn isoform) in Caco-2 cells was decreased, particularly by the two latter forms [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal physiological conditions, high selenium content in the serum is positively related to survival rate, while a decrease in serum selenium levels increases the risk of cancer and death [6]. In particular, sodium selenite (SS) is a common inorganic selenium that triggers superoxide anions to induce apoptosis in cancer cells [7, 8], demonstrating its potential anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Using 2DE‐based proteomics the influence of Se compounds on cancer cells, e.g. prostate cancer lines , HeLa cells and Caco‐2 cells , on rat plasma and on different rodent tissues has been previously investigated . However, in all these studies only effects of single selenocompounds have been evaluated.…”
Section: Introductionmentioning
confidence: 99%